Effectiveness of Using Interactive Learning Media to Improve Students' Learning Interests at State Elementary School 0406 Aek Tinga In Islamic Education Learning - Sipahutar, Nurasiah; Harahap, Ika Mustika Wati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the effectiveness of using interactive learning media in improving the learning interest of 3rd grade students of SD Negeri 0406 Aek Tinga, Sosa District on ablution worship material. This study uses a Classroom Action Research (CAR) approach consisting of two cycles, with each cycle involving planning, implementation, observation, and reflection. The subjects of the study were 30 3rd grade students consisting of 15 boys and 15 girls. Data collection was carried out through observation, questionnaires, and written tests related to students' learning interest and understanding of ablution material. The results of the study indicate that the use of interactive learning media, such as video tutorials and technology-based learning applications, can improve students' learning interest. In the first cycle, the average value of students' learning interest reached 70%, and after the use of interactive media in the second cycle, the value increased to 85%. In addition, students also showed an increase in understanding of ablution procedures, which was reflected in better test results. Thus, it can be concluded that the use of interactive learning media is effective in increasing students' learning interest in ablution worship material at SD Negeri 0406 Aek Tinga, Sosa District.